PERAN GURU SEBAGAI FASILITATOR DALAM MENUMBUHKAN MINAT MEMBACA SISWA KELAS II SDN 177 PEKANBARU - Nurhaliza Putri Sabila; Siti Quratul Ain (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the role of the teacher as a facilitator in fostering students' interest in reading. The method used in this research is descriptive qualitative. Data collection techniques and instruments are interviews, observation and documentation. Testing the validity of the data using source triangulation, technical triangulation and time triangulation. The data analysis technique used is data reduction, data presentation and conclusions. The conclusion of this study is that the teacher's role as a facilitator in cultivating students' interest in reading includes the five indicators. The first is providing learning facilities, the second is providing all learning resources, the third is acting as a partner, the fourth is carrying out the duties and responsibilities of the teacher, the fifth is not acting arbitrarily. Overall the teacher has tried to carry out his role as a facilitator in fostering students' interest in reading. The teacher's obstacle acts as a facilitator in fostering students' interest in reading, namely the lack of interest in reading in students, which originates from the students' ability to read and understand the meaning contained in the reading. Then the teacher also has problems in providing learning facilities, where the role of the library is not maximized and there are limited books or other reading materials. The solution to dealing with the obstacles faced by teachers is to create activities that can increase students' interest in reading and make a group schedule to visit the library. In addition, the teacher also applies learning methods and media that aim to build a conducive classroom atmosphere.